Canons in dialoog - M. Beyen (BMGN: Low Countries Historical Review, 2006)
Marnix Beyen, Canons in dialogue After pointing out that the idea of a national canon is completely absent when history is taught in Belgium, the author goes on to reject the whole idea of a national canon, describing it as a paternalist attempt to streamline the past according to the wishes of a well-meaning elite. Aside from viewing this idea as an unscientific over simplification of complex issues, heal so deems it to be counter productive from a social point of view. In his opinion, it threatens to alienate youngsters in the Netherlands even more from their past. An alternative approach, he argues, would be to provide more scope for an active dialogue between different, sub-culturally determined historical canons when teaching history. This article is part of the forum 'Debat over de zin of onzin van een nationale canon'.